Membangun Harmoni dalam Keluarga melalui Komunikasi Efektif - Wulandari, Ida Ayu Gde; Luh Gde Surya Kartika; Ni Nengah Selasih; Ni Wayan Arini (Sevanam: Jurnal Pengabdian Masyarakat, 2024)
The Sukinah family is shown with harmonious, happy and peaceful family members. Respecting family members and other people is the simplest and most basic thing that can be done to start the journey to achieving a successful family. Another thing that family members can do to create a happy family is to maintain physical, mental, emotional and spiritual balance as well as good communication relationships between family members. As facilitators of effective communication in relationships with children, parents can play various roles together. The absence of effective communication in the family can trigger many things, including spamming of children and teenagers, suicide, divorce, or leaving the home. To maximize effective communication in order to reach the Sukinah family within the family, counseling is held regarding effective family communication. Participants are reminded that being a good listener is one way to reach the Sukinah family. The activity was carried out in Kukuh Village, Kerambitan District, Tabanan Regency, with the activity participants being women in the village. The number of participants was 40 people who were representatives of each banjar in Kukuh Village. The method of carrying out activities is classic, where participants and resource persons meet in the same place to listen and discuss. The activity began with giving a pre-test, then continued with the presentation of material by the resource person as well as discussions and questions and answers. The activity ends with completing the post test. The results of the post-test analysis showed that as many as 98.3% of the activity participants were able to answer the post-test questions correctly, this shows that the participants were able to understand the material presented.